FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN LAYANAN RAWAT INAP LANJUTAN PESERTA BPJS KESEHATAN - Ratna Wardani (Universitas Pesantren Tinggi Darul Ulum, 2018)
Health cost becomes a significant problem of health care services in the plenary. The aim of this study was to determine the influence of attitudes, subjective norms, and perceived behavioral control of the utilization of advance services belongs to BPJS Kesehatan members.This research utilixing the cross sectional research design. The population is all inpatients participants BPJS Kesehatan at Kabupaten Kediri General Hospital for 97 respondents. The samples in this research were taken using simple random sampling technique, for 78 respondents. The independent variable is the attitude, subjektive norms, and perceived behavioral control while the dependent variable utilization of inpatient services continued.In this research, the results showed that there are 75 respondents (96.2%) who have a positive attitude, 67 respondents (85.9%) who have a positive subjective norm, 61 respondents (78.2%) who have a positive perceived behavior control and 76 respondents (97.4%) which utilizes advanced inpatient services. Results of analysis using logistic regression with α = 0.05 showed that the sig. 0,000 < 0,05 so that H0 is rejected. The conclusion of this research is attitudes, subjektive norms, and perceived behavioral control has a significant influence on the utilization of inpatient services continued. Keywords: attitude, perceived behavioral control, subjective norm, utilization of advanced inpatient services.